Health-related quality of life and ego integrity among the oldest old - Evidence from the multicenter AgeCoDe-AgeQualiDe study - Hajek, André; Forstmeier, Simon; Brettschneider, Christian; Lühmann, Dagmar; Döhring, Juliane; Wiese, Birgitt; Oey, Anke; Weyerer, Siegfried; Werle, Jochen; Pentzek, Michael; Fuchs, Angela; Röhr, Susanne; et al. (Archives of gerontology and geriatrics, 2021)
Purpose - To investigate the association between health-related quality of life and ego integrity among the oldest old. - Materials and methods - Cross-sectional data were taken from follow-up wave 9 of the multicenter prospective cohort study “Needs, health service use, costs and health-related quality of life in a large sample of oldest-old primary care patients (85+)” (AgeQualiDe). Our analytical sample comprised n = 495 observations. Mean age was 90.2 years (SD: 2.7 years). Health-related quality of life was quantified using the EQ-5D-3L questionnaire (including the visual analogue scale EQ-VAS). Ego integrity was measured using the Ego Integrity Scale. - Results - Regressions showed an association between decreased ego integrity and problems with ‘usual activities’, ‘pain/discomfort’ and ‘anxiety/depression’. Furthermore, regressions showed a marginally significant association between decreased ego integrity and problems with ‘mobility’ and a decreased EQ-VAS score. Ego integrity was not significantly associated with problems with ‘self-care’. - Conclusions - Findings stress the importance of health-related quality of life for ego integrity among the oldest old. Future studies are required to clarify the underlying mechanisms.
Gesehen am 19.10.2022